EMOTIONAL INTELLIGENCE AND MOTIVATION IN RELATIONSHIP BETWEEN FAMILY ENVIRONMENT AND TPACK ON TEACHER CAREER READINESS - Senia Paramesti; Amir Mahmud (Universitas Negeri Semarang, 2025)
Competitive competition in the world of work requires the world of education to be able to produce human resources who are ready to compete. Therefore, students need to master relevant skills and knowledge so that they can have career readiness according to industry needs. The purpose of this study is to analyze the readiness of students to become a teacher, including the family environment and the mastery of TPACK which is moderated by emotional intelligence and mediation of motivation to become a teacher. The data collection technique used questionnaires, while the data analysis techniques used were percentage descriptive analysis, inferential statistics, and multiple linear regression analysis. The results of the study showed that the family environment and mastery of TPACK had a significant positive effect on career readiness to become a teacher. And emotional intelligence can be a pure moderator variable, while motivation to become a teacher is a mediator variable that affects the readiness to become a teacher. The advice given in this study is for parents to support their children in preparing themselves to become teachers, students to improve their technological skills and confidence, understand the role of teachers, set clear goals, and manage emotions well which can support their readiness for a career as a teacher.